EVENT AND TIME IN YENIŞEHIR'DE BIR ÖĞLE VAKTI AS A MODERNIST NOVEL - HATIL, İrem (Atlas Journal, 2020)
Considering the historical process of the modernist novel in Turkish literature, it is clear that it emerged late compared to the west; However, although its birth was late, it succeeded in gaining a place with successive writer sand their successful works. One of these writers and works is Sevgi Soysal and her critical novel, Yenişehir’de Bir Öğle Vakti, written in prison. This novel, which is considered as a modernist novel in the study, has been examined in terms of "event and time" in terms of its elements. With these aspects, it has been examined whether the novel is compatible with the new modernist elements and it is aimed to find out how much it matches with those elements. In modernist novels, although the time element seems to have become shorter, it actually covers long periods with different expression techniques. The event element has almost disappeared in these novels. Rather than the event, the situations, people and their individual stance, consciousness came to the fore. Sevgi Soysal is one of the writers of the coupperiod. During this period, he was arrested while serving in TRT and during his detention period he wrote Yenişehir’de Bir Öğle Vakti. With this novel, Soysal has revealed Ankara of the period and different human landscapes from different segments in the process of collapse of a poplar. In this study, the event and time elements of Sevgi Soysal's novel, Yenişehir’de Bir Öğle Vakti, have been tried to analyze.